156k views
1 vote
Hey can you please help me posted picture of question :)

Hey can you please help me posted picture of question :)-example-1

2 Answers

6 votes
sorry dont really know :/
User Cowlinator
by
6.0k points
2 votes
Answer:
The roots of the equation are -4 and -5

Step-by-step explanation:
The general form of the quadratic equation is:
ax² + bx + c = 0
The given equation is:
3x² + 27x + 60 = 0
By comparison, we could find that:
a = 3
b = 27
c = 60

Now, to get the roots we would use the quadratic formula shown in the attached image.

By substituting, we would find that:
either x =
(-27+ √((27)^2-4(3)(60)) )/(2(3)) = -4

or x =
(-27- √((27)^2-4(3)(60)) )/(2(3)) = -5

This means that the roots of the equation are -4 and -5

Hope this helps :)

Hey can you please help me posted picture of question :)-example-1
User Zerocog
by
6.2k points